Test of Hypersensitivity and Antagonistic Reaction of Endophytic Bacteria from Klutuk Banana (Musa balbisiana) - Dewianty, Ratih; Rahayu, Triastuti; Sidiq, Yasir (BIOEDUSCIENCE, 2023)
Background: Plants’ response and antagonistic reaction against disease-causing organisms are two crucial characteristics of Plant Growth Promoting Bacteria (PGPB). Seventeen endophytic bacteria have been isolated from Musa balbisiana. However, the plants’ reaction against these isolates and their antagonistic activities against disease-causing organisms remained unknown. This study aims to (1) determine the sensitivity effect of endophytic bacteria isolates to tobacco and (2) test the antagonism of endophytic bacteria isolates against the blast disease actor, namely Pyricularia oryzae. Method: Sensitivity tests were performed by inoculating bacterial isolates into tobacco leaves with infiltration. Bacterial isolates were prepared with a minimum OD 600: 0.5. Then, a milliliter volume of each isolate was infiltrated into tobacco leaves from the abaxial side using a 3 mL syringe. The lesion on the tobacco leaves was observed seven days after inoculation (DAI). The antagonism test was carried out by growing Pyricularia oryzae on a PDA plate for seven days, subsequently transferred to an NA medium for three days then inoculated with endophytic bacteria. The assessed parameter of the antagonistic test was the formation of an inhibitory zone between endophytic bacteria and Pyricularia oryzae at 4 DAI. Results: No hypersensitive reaction of tobacco leaves against K117, K324, K38, K86, K18, K28, K102 isolates inoculation at 7 DAI. Furthermore, the antagonistic test indicated that all isolates inhibited the growth of Pyricularia oryzae, with the range of inhibition from 32.36 to 40.46%. Implication: Thus, these results revealed the PGPB characteristics in the newly isolated endophytic bacteria from the banana.